THE INTEGRATION OF HOTS IN THE LESSON OBJECTIVES OF ENGLISH TEXTBOOK FOR SECOND GRADERS - Ferina Rizkiani (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
High Order Thinking Skills have a major influence on the pupils because they must be able to analyze, evaluate, and create their knowledge appropriately. Furthermore, Bloom’s taxonomy verbs usually are attached in the lesson objectives of the English textbook. They appear to indicate and to determine what pupils have to achieve by the end of the lesson. This research purposes to explore the integration of HOTS in the lesson objectives of the English textbook which is being used by second graders of elementary school at SDN Pegangsaan Dua 07 Pagi. This research employed content analysis which refers to document analysis and the data came from the English textbook entitled “I Love Jakarta’ by Tiga Serangkai for second graders. It was analyzed by employing Anderson and Krathwohl’s taxonomy descriptors. The result revealed that the integration of high order thinking skill in English textbook “I Love Jakarta” for second graders is limited. It is suggested that the English teacher and the editor of the English textbook collaborate and cooperate by conducting open discussions to novelize